PENGARUH MODEL PEMBELAJARAN TALKING STICK BERBANTUAN MEDIA KOTAK RAHASIA NEGARA KITA TERHADAP PEMAHAMAN - Salsabila Alya; Kartika Yuni Purwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Talking Stick learning model assisted by the “Kotak Rahasia Negara Kita” media on the conceptual understanding of fifth-grade elementary school students. The study employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The research subjects consisted of two groups, namely the experimental class and the control class, which were selected through purposive sampling. Data collection techniques were carried out using tests to measure students’ conceptual understanding through pretest and posttest in the form of essay questions based on conceptual understanding indicators. In addition, non-test techniques such as observation, questionnaires, interviews, and documentation were used as supporting data. Data analysis was conducted using SPSS through validity tests, reliability tests, item difficulty, discrimination index, normality test, homogeneity test, and hypothesis testing using independent sample t-test and simple linear regression. The results showed that there was a significant effect of the Talking Stick learning model assisted by the “Kotak Rahasia Negara Kita” media on students’ conceptual understanding. This is indicated by the t-test significance value of 0.004 (<0.05) and the regression significance value of 0.024 (<0.05). Therefore, the learning model is effective in improving students’ conceptual understanding.